1992
DOI: 10.1016/0266-7681(92)90022-t
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the Ruptured Distal Tendon of the Biceps Brachii

Abstract: The biceps brachii is the main supinator of the forearm. Unless the ruptured distal tendon is reattached to its correct anatomical site on the radial tuberosity, its action cannot be restored. We report four cases treated surgically, who all regained full forearm function, and on the basis of our experience suggest a simple method of reattaching the tendon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…11,15,33 In symptomatic patients, nonanatomic biceps-to-brachialis repair is an option. Earlier reports 14,27,38 have pointed out the inefficacy of this procedure to restore supination strength. In a recent study using isokinetic testing, Klonz et al 17 found that half of their patients with biceps-to-brachialis fixation lost more than 50% of supination strength.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…11,15,33 In symptomatic patients, nonanatomic biceps-to-brachialis repair is an option. Earlier reports 14,27,38 have pointed out the inefficacy of this procedure to restore supination strength. In a recent study using isokinetic testing, Klonz et al 17 found that half of their patients with biceps-to-brachialis fixation lost more than 50% of supination strength.…”
Section: Discussionmentioning
confidence: 95%
“…A biceps-tobrachialis repair is the simpler salvage option in such instances, but this procedure does not restore supination strength. 5,14,17,27,38 It is thus a suboptimal solution for patients such as manual workers and athletes who have high functional demands in supination.Our current indication for distal biceps reconstruction is the inability to approximate the biceps stump to the bicipital tuberosity with the elbow in less than 70°o f flexion in a patient with high functional demands in supination. We present the surgical technique and results of distal biceps reconstruction in chronic ruptures through a single anterior approach using Achilles tendon allograft.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…36 Repair of the tendon to the brachialis muscle and bone using sutures tied over a bony bridge, suture anchors, screw and washer, endobutton, and the use of an interference screw have all been described. 6,9,15,25,27,36,37,39,[41][42][43] Whichever technique is chosen, performing an anatomic repair should always be the goal to best restore function. 24 Anatomy textbooks provide a vague description of the insertion of the tendon onto the radial tuberosity, but they fail to address the footprint of the tendon on the tuberosity or the rotational position of the tuberosity on the radius.…”
mentioning
confidence: 99%
“…Both operative and non-operative treatment has been reported in the literature [25,26,48,50,52,53,57]. Nonoperative treatment has consistently shown poor objective strength measurements, with significant losses of flexion and supination power [2,6,22,23,28,29,30,39].…”
mentioning
confidence: 99%